Intercultural Communication And Co-Creation In Tourist Satisfaction: Asian–European Perspectives In Mandalika, Lombok - Muhammad Mujahid Dakwah; Mohammad Najib Roodhi; Baehaqi Baehaqi (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This study investigates how intercultural communication competence (ICC), communication skills (CS), quality of interaction (QI), and experience co-creation (ECC) influence tourist satisfaction (TS) in Mandalika, Indonesia. The research aims to examine both direct and indirect effects, including the mediating roles of CS and QI, and the moderating role of ECC. The study also compares responses between Asian and European tourists to uncover cultural differences. Using an explanatory research design, data were collected through structured questionnaires from 581 tourists and analysed using PLS-SEM and Multi-Group Analysis with SmartPLS 4.0.3. The results show that ICC significantly affects TS through CS and QI in the full sample but not within cultural subgroups. ECC significantly strengthens the effect of QI on TS across all groups. This study contributes theoretically to intercultural communication and offers practical guidance for destination managers to adopt culturally adaptive and co-creative service strategies.